CÂNONE LITERÁRIO E HISTÓRIA DA LITERATURA - Zilberman, Regina (Organon, 2012)
This essay assumes a hypothetical independence of Rio Grande do Suland, from this viewpoint, describes the outline of “gaúcha” literature, which wouldbegin the “‘sul-rio-grandense literary canon”. Afterwards, this hypothesis is argued,by showing the duality in the literary production of Rio Grande do Sul: following themodels established by the center of the country, or accepting the “Regionalism” andthus becoming marginal.